Use of Electronic Resources in Teaching Religion in Higher Education: Best Practices from the SULSIT, Bulgaria - Shapkalova, Svetla; Nazarska, Georgeta (Central European Journal of Educational Research, 2020)
This paper describes actually methodical attempts to use library electronic resources in academic education. Some opportunities for improving the teaching of religious cultural heritage and for diversify the methods of assessment of students in Bulgarian universities are commented. The text describes the personal experience of the authors with students of 3rd-4th grades from the State University of Library Studies and IT (SULSIT), Bulgaria. Among the “best practices” are tasks of performing on-line survey of digital resources of periodicals from the digital resources of the “St. St. Cyril and Methodius” National Library, of making content analysis of the database on a particular subject, of preparing bibliographic descriptions of the new discovered resources, of writing historical analyses, of generating thematic bibliographies on topics related to religion, using the resources of the electronic catalogs of regional public libraries in the country.